Pelatihan Peningkatan Dasar Kepemimpinan Untuk Membentuk Jiwa Kepemimpinan Yang Kreatif Dan Inovatif Pada Pengurus Yayasan Darul Furqon Ramadhan Desa Cibadung Gunung Sindur - Rahmayanti Rahmayanti; Zaki Zainal Arifin; Annie Rufeidah; Dyas Mulyani Benazir; Riri Oktarini (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
Leadership is the ability of someone in an organization to lead or guide others or members of the organization. The Qur'an memorization boarding school (PPA) "Darul Furqon Ramadhan" located in Saga Bulak Village, Rt 002/07, Cibadung Village, Gunung Sindur Subdistrict, Bogor Regency, West Java Province is a place for social propaganda in the Bulak Saga village, where the foundation's activities are namely having recitation activities, tahfidz quran, orphan compensation, financing orphans and dhuafanya, so that in the activities of the Foundation DFR requires skilled management staff, communicative, and has a creative and innovative leadership spirit so that the activities of the DFR foundation can run in accordance with the goals of the Foundation. Leadership is the way a leader influences the behavior of subordinates to want to work together and work productively to achieve organizational goals. Therefore, the DFR Management must have the task of developing the performance of the personnel, especially improving the competence of the personnel in terms of leadership.Keywords: Leadership, leadership style, creative and innovative.